From the Theory of Archival Narrative to the Practice of Archival Blogging: Why the Characteristics of Narrative Matter - Patti, Harper (Université d'Ottawa / University of Ottawa, 2014)
This thesis aims at defining the archival narrative from the discourse between archivists and historians writing on “archives as subject”. The objectives of this thesis are to identify and define the characteristics of archival narrative and to apply these characteristics to archival blogging. Qualitative and reflective, this research conducted a comprehensive and systematic literature review on “archives as subject” to produce a conceptual framework that defines archival narrative and its characteristics. A content analysis was also conducted to determine how the characteristics defining archival narrative are represented within archival blogs. The content analysis identifies, refines and defines the characteristics of archival narrative. As archives evolve in the digital world, social media and the demand for increased patron engagement, archivists’ must recognize their own expertise while sharing the characteristics of archival narrative. This will contribute to a more transparent and accountable archival profession.
Keywords: Archival Narrative; Socia media; Archives as Subject; Blogging; Characteristics of narrative